Consensus Recommendations for the Use of Hyperdiluted Calcium Hydroxyapatite (Radiesse) as a Face and Body Biostimulatory Agent - de Almeida, Ada Trindade; Figueredo, Vinicius; da Cunha, Ana Lúcia Gonzaga; Casabona, Gabriela; Costa de Faria, Joana Ribeiro; Alves, Emerson Vicente; Sato, Mauricio; Branco, Adeíza; Guarnieri, Christine; Palermo, Eliandre (Plastic and reconstructive surgery. Global open, 2019)
BACKGROUND:Calcium hydroxyapatite (CaHA) is a well-established collagen stimulator. In recent years, it has been increasingly used in hyperdiluted form as a biostimulatory agent rather than a volumizing filler to improve skin quality and firmness in both facial and corporal areas. However, guidelines on the techniques required to achieve optimal results are still lacking. The objective of this study was to develop a consensus recommendation for the safe and effective use of hyperdiluted CaHA for face and body biostimulation. METHODS:A team of 10 experts with extensive experience in dermal fillers and biostimulatory treatments for facial and body rejuvenation convened for a live meeting. Consensus was defined as approval by 70%–89% of all participants, whereas agreement of ≥90% denoted strong consensus. RESULTS:For most items, the group achieved a majority consensus. Recommendations have been provided for the face, neck, décolletage, buttocks, thighs, arms, abdomen, knees, and elbows with detailed injection techniques, providing information on insertion points, dosages, and volumes for both needle and cannula injections as well as the number of treatment sessions and intervals. CONCLUSIONS:The expert consensus supports and provides guidance for the use of CaHA as a biostimulatory agent for face and body rejuvenation. However, further clinical studies are necessary to provide physicians with the best evidence for the best treatment practices.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.